Pastoral systems and cultures in transition - Leeuw, Jan de (International Livestock Research Institute, 2011)
Jan de Leeuw from ILRI reflects on the recent conference in Addis Ababa on the future of pastoralism in Africa. He concludes that pastoral systems in Africa are very much in transition. He notes that external influences on pastoralism (education, religion, land rights etc) are much more visible than in the past; the "full mobility" pastoralism that we knew is changing. He comments on so-called 'land grabbing' and pastoral development; and the particular challenges of development in drylands where the interventions of governments and others are increasingly impacting on the livelihoods of pastoralists. The Addis Ababa conference (21-23 March 2011) was organized by the Future Agricultures Consortium with Tufts University.